Treatment of Epiphora in Connection with Endolacrimal Surgery using Trephines: New and Overview Data - Pimentel de Figueiredo, A. R.; Almeida Dantas, R.; Piffaretti, J.-M.; Haefliger, I. O. (Klinische Monatsblätter für Augenheilkunde, 2013)
Background. To provide new and to summarize published data on endolacrimal surgery with Piffarettiʼs trephines, in particular in patients having patent lacrimal drainage system (syringing) and epiphora resistant to medical treatments.Patients and Methods. From two tertiary referral centers (Basel/Switzerland; Belo Horizonte/Brazil), 126 patients undergoing endolacrimal surgery with Piffarettiʼs trephines, combined, when clinically indicated, with other procedures known to improve epiphora (canthoplasty/pexie and/or conjunctivochalasisplasty).Results. I) A study (Basel) in 17 patients showed one-year after surgery marked epiphora symptomsʼ improvement in 88 % (15/17) of patients, 65 % (11/17) being symptom-free. II) Unpublished data (Belo Horizonte) in 42 patients found 81 % (34/42) symptom-free six-months after surgery. Dacryoscintigraphy illustrated postoperative tearsʼ clearance improvement. III) Unpublished data (Belo Horizonte) in 45 patients solely undergoing endolacrimal surgery for complete ductal obstruction found symptom-free, six-months after surgery, 27 % (8/30) of patients with preoperatively enlarged lacrimal sac and 80 % (12/15) with none-enlarged sac (p < 0.01, Fisherʼs test). IV) A study (Basel) in 22 epiphora patients reported no correlation (p = 0.62, rho −0.11, Spearman) between preoperative basal Schirmerʼs test II (oxybuprocain-HCL 0.4 %) values and one-year surgical outcome. Patients with preoperative Schirmerʼs testʼs values ≤ or > 6 mm had similar mean postoperative symptomsʼ improvement (82 ± 30 %, n = 11 vs. 76 ± 34 %, n = 11, p = 0.97, Mann-Whitney).Conclusions. Endolacrimal surgery with Piffarettiʼs trephines, sometimes combined, when clinically indicated, with other procedures also known to ameliorate epiphora, can in particular improve (different conditions, surgeons, centers) epiphoraʼs symptoms resistant to medical treatments in patients with patent lacrimal drainage system, and this apparently, even when pre-operative basal Schirmer-test values are low. By enlarged lacrimal sac, outcome is poor.
Keywords: lacrimal surgery; watery eye; tearing eye; balloon dacryocystoplasty; laser dacryocystorhinostomy; dacryocystorhinostomy; endonasal dacryocystorhinostomy; Jonesʼ tube; dry eye syndrome; keratoconjunctivitis sicca